One step DNA amplification of mammalian cells in picoliter microwell arrays. Issue 5 (21st January 2019) - Liu, Wenwen; Li, Zhao; Liu, Yuanjie; Wei, Qingquan; Liu, Yong; Ren, Lufeng; Wang, Chenyu; Yu, Yude
Abstract : One-step PCR of a single cell in a picoliter microwell array was developed and applied to detect a target with the sensitivity of a single copy. Abstract : We developed a strategy for direct DNA amplification of single cells on a PEG-modified silica chip with 30 600 picoliter-sized microwells. HPV-positive cells in heterogeneous populations were successfully detected with high accuracy sensitivity as high as single copy.